(untitled) (Revista Internacional de Formação de Professores, 2016)
The child of today lives steeped in a world made of symbols which uses, from a very early age, to unlock and see the world. In other words, we can say that, for the "building your knowledge", the child relates to other children, adults and the environment in which they live, using different languages. Our goal is to discuss how this construct from a freinetiano look, since, in this proposal the different languages: verbal, graphic, bodily, musical, plastic writing are encouraged and embraced as part of all activities. To introduce in the school environment, educational techniques such as free text, the newspaper, the mail, the work plan, the class library, the cooperative Council, Célestin Freinet endowed the classroom of structural and functional conditions for work with all languages, based on freedom of expression, in the exchange of ideas, in the experimental tateio, the creative work and cooperation.